Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1186/1297-9716-43-77
|View full text |Cite
|
Sign up to set email alerts
|

The interpretation of disease phenotypes to identify TSE strains following murine bioassay: characterisation of classical scrapie

Abstract: Mouse bioassay can be readily employed for strain typing of naturally occurring transmissible spongiform encephalopathy cases. Classical scrapie strains have been characterised historically based on the established methodology of assessing incubation period of disease and the distribution of disease-specific vacuolation across the brain following strain stabilisation in a given mouse line. More recent research has shown that additional methods could be used to characterise strains and thereby expand the defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 38 publications
(77 reference statements)
6
26
0
Order By: Relevance
“…By definition, the phenotype is host specific and includes a very large number of parameters which may evolve over time as new techniques are applied. For practical purposes in TSEs the parameters that are currently considered to define phenotype are incubation period, clinical signs, and quantitative aspects of vacuolation which give rise to lesion profiles, IHC deposition patterns and Western blot characteristics [31][32][33] . For the purposes of this review different phenotypes in the original host are considered as different TSE strains ie BSE, H-type BSE and L-type BSE in cattle, and classical and atypical scrapie in sheep.…”
Section: Tse Disease and Strain Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…By definition, the phenotype is host specific and includes a very large number of parameters which may evolve over time as new techniques are applied. For practical purposes in TSEs the parameters that are currently considered to define phenotype are incubation period, clinical signs, and quantitative aspects of vacuolation which give rise to lesion profiles, IHC deposition patterns and Western blot characteristics [31][32][33] . For the purposes of this review different phenotypes in the original host are considered as different TSE strains ie BSE, H-type BSE and L-type BSE in cattle, and classical and atypical scrapie in sheep.…”
Section: Tse Disease and Strain Characterisationmentioning
confidence: 99%
“…However, after experimental transmission of a TSE to wild type or transgenic rodents a single or multiple phenotypes may emerge in a single mouse line, leading to the laboratory definition of a strain. According to this definition, classical scrapie includes several strains as various distinct phenotypes can be identified in mice [33][34][35] . In contrast every time a source of atypical scrapie has been bioassayed in mice a single phenotype has been detected suggesting that atypical scrapie is attributed to a single strain 36,37) .…”
Section: Tse Disease and Strain Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on strain typing studies in mice it is well documented that more than one TSE strain is responsible for Classical scrapie in sheep Bruce, 2003;Thackray et al, 2011Thackray et al, , 2012Beck et al, 2012a;Cassard et al, 2014). However, the exact number of Classical scrapie strains is unknown despite characterisation of several scrapie isolates in both wild type and transgenic mouse models.…”
Section: Agent Strains In Sheepmentioning
confidence: 99%
“…Therefore they retain little resemblance to the properties of the agent in the sheep, and cannot be considered to comprehensively represent the field situation. Since the BSE epidemic, further characterisation of naturally occurring Classical scrapie cases that were detected after 1985 was initiated to identify strain variation in natural Classical scrapie using both wild type and transgenic mouse models (Bruce, 2002;Bruce et al, 2002;Beck et al, 2012a;Thackray et al, 2011Thackray et al, , 2012Cassard et al, 2014). Remarkably, the studies conducted in wild type mice after 1985 revealed novel strains in addition to the 20 that were known historically, suggesting that there may be evolution of Classical scrapie strains (Bruce et al, 2002;Beck et al, 2012a).…”
Section: Agent Strains In Sheepmentioning
confidence: 99%